1999
DOI: 10.1016/s0194-5998(99)70287-1
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Psychosocial Correlates of Head and Neck Cancer: A Review of the Literature

Abstract: This article reviews recent literature on the physical and psychosocial correlates of head and neck cancer, with a focus on quality-of-life issues, rehabilitation outcomes, and changes in the literature from the previous decade. These studies have shown that head and neck cancer has an enormous impact on the quality of life of patients. The most important physical symptoms are speech problems, dry mouth and throat, and swallowing problems. Pain is also frequently reported. Disturbances in psychosocial function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
124
0
11

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(141 citation statements)
references
References 67 publications
3
124
0
11
Order By: Relevance
“…Tal fato tem a importân-cia de trazer para este estudo a corroboração de que avaliar qualidade de vida é tarefa recente que tem tido um significativo crescimento ao longo do período (Batel-Copel et al, 1997;Boer et al, 1999;Camilleri-Brennan & Steele, 1998).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Tal fato tem a importân-cia de trazer para este estudo a corroboração de que avaliar qualidade de vida é tarefa recente que tem tido um significativo crescimento ao longo do período (Batel-Copel et al, 1997;Boer et al, 1999;Camilleri-Brennan & Steele, 1998).…”
Section: Discussionunclassified
“…No que se refere às características metodológicas dos estudos analisados, apenas cinco estudos eram estudos de coorte, o que traz para esta revisão, à semelhança do que se encontra em Boer et al (1999) e Gotay & Muraoka (1998), a possibilidade de mostrar que não existe um número significativo de estudos observacionais prospectivos que possam abarcar com maior especificidade a questão da qualidade de vida em pacientes laringectomizados, o que não se coaduna com o fato de que a sobrevida na maioria dos casos é considerada satisfatória (65% de taxa de sobrevida global em cinco anos).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Vital functions can be affected and minor disturbances of anatomy by surgery or chemo/radiation therapy may lead to significant dysfunction and disfigurement, and hence to psychosocial complaints (De Boer et al, 1999). Recent literature suggests that such psychosocial consequences are not only observed in H&N cancer patients themselves.…”
Section: Introductionmentioning
confidence: 99%
“…Although tumour sites (larynx, oral cavity, oropharynx, sinus and nose and the salivary glands) are known to affect crucial functions, such as the ability to breath, speak, eat and smell, until recently little has been known about how such impairments impact on the HRQL of H&N cancer patients.The first HRQL studies of H&N cancer patients were crosssectional or retrospective (Pruyn et al, 1986;de Boer et al, 1999), but during the last few years prospective studies have also been published (Jones et al, 1992; List et al, 1996;Deleyiannis et al, 1997;Funk et al, 1997;Hammerlid et al, 1997;Hammerlid et al 1997; Morton, 1997; Hammerlid et al, 1998; Hammerlid et al, 1998;Bjordal et al, 1999; de Graeff et al, 1999; de Graeff et al, 1999;Deleyiannis et al, 1999; List et al, 1999; Rogers et al, 1999). These studies have been performed with validated questionnaires and have consistently shown that H&N cancer patients' HRQL is significantly below norm values at diagnosis and decreases during and immediately after treatment.…”
mentioning
confidence: 99%